Preliminary Report on the Torngat Archaeological Project - Fitzhugh, William (ARCTIC, 1980)
The Torngat Archaeological Project conducted two seasons of field work in northern Labrador in 1977-78. Surveys by boat and ground crews ranging from Nain to the Button Islands located nearly 350 archaeological sites and gathered data from many geological and botanical stations. Cultures represented in this region include all of the known arctic groups (Pre-Dorset, Dorset, Thule, and Labrador Inuit) and northern Indian cultures (Maritime Archaic, Saunders, and Point Revenge) known from the central Labrador coast. In addition to contributing to knowledge of 6000 years of culture history in this environmental and cultural frontier, the project is investigating environmental relationships and processes of culture change which have affected Eskimo, Indian, and European settlement. This paper presents a project overview and discusses TAP goals, physical setting, analytical orientation, field methods, and preliminary conclusions.